Uncovering the Molecular Landscape of Secreted Phosphoprotein 1 and Its Expression Network in Kidney Renal Papillary Cell Carcinoma - Amukti, Danang Prasetyaning; Pratami, Ria Indah; Bachri, Moch Saiful; Estiningsih, Daru (Biomedical Sciences and Clinical Medicine, 2025)
Objective This study aims to investigate the expression pattern of Secreted Phosphoprotein 1 (SPP1), its prognostic relevance, and the associated co-expression gene network in kidney renal papillary cell carcinoma (KIRP). Methods Publicly available transcriptomic and clinical datasets were analyzed using GEPIA, UALCAN, and the GTEx Portal. SPP1 expression levels in KIRP versus normal kidney tissues were evaluated, followed by Kaplan–Meier survival analysis stratified by ethnicity, gender, and body weight. Co-expression analysis was performed to identify genes significantly correlated with SPP1 and to explore their potential biological functions. Results SPP1 expression was significantly upregulated in KIRP tissues compared with normal kidney tissues, consistent with GTEx data showing naturally high expression in kidney cortex and medulla. High SPP1 expression was associated with poorer overall survival, particularly among Caucasian patients, while no significant survival differences were observed by gender or body weight. Ten genes strongly co-expressed with SPP1, MLLT3, AKIRIN2, YIPF1, SESTD1, LAMC1, FAS, ABCC3, MTHFD1L, ANXA2P2, and ARHGAP29 were identified, many of which are implicated in cell adhe-sion, migration, extracellular matrix remodeling, and apoptosis resistance. Conclusions SPP1 is markedly overexpressed in KIRP and correlates with unfavorable prognosis, highlighting its potential as a diagnostic and prognostic biomarker. The identified SPP1-associated co-expression gene network may offer novel insights and therapeutic targets for improving molecular-based interventions in KIRP.